Psychosocial care center users and their experience of living with a mental illness - Nagaoka, Ana Paula; Furegato, Antonia Regina Ferreira; Santos, Jair Licio Ferreira (Revista da Escola de Enfermagem da USP, 2011)
With a view to the changes in psychiatric care, the objective of this study was to learn about the opinion of patients, users of a Psychosocial Care Center, about their treatment, their experience of living with a mental illness and its psychosocial implications. The results were then matched with their social-demographic and clinic profile. A descriptive exploratory study was performed, where 65 patients with mental illnesses being treated in a center in Pindamonhangaba-SP and 53 of their relatives answered a semi-structured questionnaire. The results showed that patients with mental illnesses and family problems recognize that the disease has changed their lives, but their opinion differ about the degree of difficulties they have in doing their everyday activities. Although they have been treated for years through this extra-hospital individualized system, they know little about their disease. It was observed that 62% of them have severe diseases, but both groups showed a special ability of dealing their adversities. This study contributes with important information for mental health nursing practitioners.